Development of pole-and-knife springs system for harvesting oil palm fruit - Lee, Min Khuan (2023)
Efficient harvesting of oil palm fruit is crucial for the industry's sustainability and profitability. Traditional manual harvesting methods have been used for many years, but they are tiring, time-consuming, and physically demanding. To address these issues, this project aims to develop a prototype for harvesting oil palm fronds more efficiently and reduce fatigue experienced by the worker. The developed prototype consists of a sickle with a specialized handle which provide hammering effect that helps to cut the frond and avoid the sickle get stuck problem. It’s also consists of mechanical spring to ensure the smooth cutting process that help to reduce fatigue of the harvester. The prototype was tested for its functionality and feasibility using a digital hanging balance to measure the force required to pull the frond and a stopwatch to record the time taken to cut off a single frond. The results show that the force required to pull the frond ranges from 5.07 kg to 7.01 kg, with an average force of 6.2 kg or 60.83 N. The time taken to cut off a single frond ranges from 4 seconds to 11 seconds, with an average of 7.2 seconds. In short, this project has successfully developed a prototype for harvesting oil palm fronds more efficiently and safely compared to traditional methods. The prototype has been tested for its functionality and feasibility, and the results show its potential for improving the harvesting process. Further field testing and improvements can be made to enhance the prototype's performance and effectiveness.